The Law of Stare Decises: Ijthihad in Islam vs Institutionalized Taqlid in Pakistan - Shaista Naznin; Sobia Bashir; Abdus Samad Khan (Dialogue Social Science Review (DSSR), 2025)
Different legal systems across the world reflect the great variance in States’ historical and cultural experiences. A distinct system of law known as common law has been developed over lands over the period establishing the fundamental components of the common law system. Some legal scholars calls the birth of legal traditions a result of a historical accident. The doctrine of stare decisis became well established in common law. Under the doctrine of stare decisis, judges were bound primarily by precedents established by previous judgments.